2022
DOI: 10.1186/s12981-022-00462-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efavirenz levels in blood and hair with pharmacy refills as measures of adherence and predictors of viral suppression among people living with HIV in Nigeria

Abstract: Background Strategies to support adherence are constrained by the lack of tools to objectively monitor medication intake in low-resource settings. Pharmacologic measures are objective, but pharmacy refill data is more accessible and cost-efficient. This study compared short-term and long-term efavirenz (EFV) drug levels with pharmacy refill adherence data (PRA) and evaluated their ability to predict viral suppression among people living with HIV in Nigeria. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…With a retrospective study design, the measure of self-reported missed ART doses at each refill visit was the best variable that we could utilize as a proxy for adherence in our study. Future studies should consider using objective medication adherence measures in the design stage to minimize potential measurement bias, whether that is continued use of dried blood spots 22 or alternatives such as hair samples, 23 electronic adherence monitors, 24 and ingestible sensors. 25 Limitations of this study included a small sample size resulting in limited statistical power, very specific time periods corresponding to changing COVID-19 alert levels during the first COVID-19 wave in South Africa resulting in limited generalizability, and self-reported ART adherence resulting in measurement error (internal validity) concerns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a retrospective study design, the measure of self-reported missed ART doses at each refill visit was the best variable that we could utilize as a proxy for adherence in our study. Future studies should consider using objective medication adherence measures in the design stage to minimize potential measurement bias, whether that is continued use of dried blood spots 22 or alternatives such as hair samples, 23 electronic adherence monitors, 24 and ingestible sensors. 25 Limitations of this study included a small sample size resulting in limited statistical power, very specific time periods corresponding to changing COVID-19 alert levels during the first COVID-19 wave in South Africa resulting in limited generalizability, and self-reported ART adherence resulting in measurement error (internal validity) concerns.…”
Section: Discussionmentioning
confidence: 99%
“…With a retrospective study design, the measure of self-reported missed ART doses at each refill visit was the best variable that we could utilize as a proxy for adherence in our study. Future studies should consider using objective medication adherence measures in the design stage to minimize potential measurement bias, whether that is continued use of dried blood spots 22 or alternatives such as hair samples, 23 electronic adherence monitors, 24 and ingestible sensors. 25…”
Section: Discussionmentioning
confidence: 99%
“…Sample size calculation for the study was based on proportion of 27% of non-adherence reported for pharmacy refill records from 2 African studies. [18,19] Assumptions made in the sample size calculation were, 5% precision, 5% type 1 error, and population size < 10,000. was The calculated sample size was ninety-one (91), and 100 persons were assessed for study participation eligibility. Four of those assessed were ineligible because they were not on tenofovir-based ART regimens while 2 persons declined providing consent.…”
Section: Methodsmentioning
confidence: 99%